Evaluating Prophylactic measures for the prevention of Surgical site infection. A Multicentric Study - Dr Sankar Prasad Saikia,Dr Lakhyajit Pait,Dr prakash kalita (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Surgical site infection (SSI) is still a leading cause of postoperative morbidity,prolonging hospital stay and healthcare expenditure. Although evidence-based guidelines are available, prophylactic practices remain inconsistent between centers and specialties.